Genotypic and phenotypic portrait of Candida albicans clinical isolates colonizing the airways of patients with cystic fibrosis. Issue 12 (17th December 2021) - Gnaien, Mayssa; Kallel, Aicha; Khalsi, Fatma; Hamouda, Samia; Smaoui, Hanen; Khemiri, Monia; Hadj Fredj, Sondes; Messaoud, Taieb; Boussetta, Khadija; Kallel, Kalthoum; d'Enfert, Christophe; Bougnoux, Marie-Elisabeth; et al.
Abstract : Candida albicans colonizes the respiratory tract of patients with Cystic Fibrosis (CF). It competes with CF-associated pathogens, such as Pseudomonas aeruginosa and Staphylococcus aureus, and contributes to disease severity. We serially recovered 160 C. albicans clinical isolates over a period of 30 months from the sputum of 23 pediatric and 2 adult antifungal-naive CF patients at Children's Hospital Tunis and characterized the genotype and phenotype of a subset of strains using multilocus sequence typing (MLST) and growth assays on multiple stress-, filamentous growth- and biofilm-inducing media. Out of 16 patients regularly sampled for at least 9 months, 8 and 4 were chronically and transiently colonized with C. albicans, respectively. MLST analyses of 56 strains originating from 15 patients indicated that each patient was colonized with a single strain, while 8 patients (53%) carried isolates from clade 4 known to be enriched with strains from Middle East-Africa. A subset of these isolates with the same sequence type and colonizing 3 unrelated patients displayed altered susceptibility to cell wall-perturbing agents, suggesting changes in cell wall structure/function during growth in the CF lung. We also observed differential ability to filament and/or form biofilms in a set of identical isolates from clade 10 sampled over a period of 9 months in a pediatric CF patient, suggesting alterations in phenotypes associated with virulence. Our findings will rely on future whole-genome sequencing analyses to identify polymorphisms that could explain the emergence of new traits in C. albicans strains thriving in the CF host environment.